Determining the risk of pregnancy and childbirth complications in women with initially normal body weight depending on weight gain during the gestational period - Tatyana Yu. Pestrikova; Tatyana P. Knyazeva; Elena A. Yurasova (LLC "MEDIAFORMAT", 2023)
Aim. To study the results of the course and outcomes of pregnancy in women depending on weight gain and to determine the risk of complications of the gestational period. Using the continuous sampling method, we conducted a retrospective study of the outcomes of pregnancy and childbirth in 1080 women with initially normal body weight. The initial body mass index in pregnant women of the survey group was in the parameters of 18.5-24.9. Depending on the recommended (11.5-16.0 kg) weight gain, pregnant women were divided by us into 3 subgroups: MG; GS1; GS2. The MG (363 people) included pregnant women whose total body weight gain during the entire pregnancy corresponded to the recommended weight gain parameters (11.5-16.0 kg). GS1 (543 people) included pregnant women whose total body weight gain was below the reference values (11.5 kg). GS2 (174 people) included women whose weight gain during pregnancy exceeded the reference values (16.0 kg).was carried out using the polymerase chain reaction method (Kvant-21 test). Results. With an excess of the recommended weight gain in women, parameters in which the relative risk index was more than 2 were found to be 3.5 times more than in women with a deficiency in body weight gain. These include iron deficiency anemia (8.57); gestational arterial hypertension (2.59); pregnancy-induced edema (3.2); pathology of the urinary system of inflammatory origin (3.4); ZRP (2.63); the birth of infants with a body weight of 2000 to 2499 g (2.76) and a body weight of 4500-4999g (2.77). Conclusion. Our results suggest that excess weight gain during pregnancy, even against the background of normal initial body weight, is a risk factor that has a negative impact on the condition of women and infants, to a greater extent than lack of weight gain. However, it should be noted that at present there is a certain trend towards an increase in the number of pregnant women with a lack of weight gain, which also carries certain risks for their health, although to a lesser extent than excess weight gain.